Pengaruh E-Wom Dalam Konten Media Sosial Instagram Kepada Minat Pembelian Dengan Brand Awareness Sebagai Variabel Intervening (Studi Kasus Pada Mixue Kota Malang) - Lutfi, Ilham Azizul; Wahono, Budi; Basalamah, Muhammad Ridwan (UNIVERSITAS ISLAM MALANG, 2024)
Abstract From January to April 2023, the Mixue franchise went viral due to its very rapid development in Indonesia. These contents can increase brand awareness of a brand of a product or service. Increasing brand awareness of a brand can create purchasing interest in someone who sees the content. The purpose of this study is to examine the effect of EWOM on Instagram on purchasing interest with brand awareness as an intervening variable. This study is a rare study on the analysis of EWOM and social media factors in the form of brand awareness that influence purchasing interest in Mixue Malang so that it can be a reference in academic aspects and managerial knowledge. The purpose of this study was to analyze the effect of EWOM on Instagram on purchase intention with brand awareness as an intervening variable. The study design is quantitative. This study uses primary data as data provider. This study uses a questionnaire data collection method. This study's population consisted of Business and Economic Faculty students from the 2022 batch at Universitas Islam Malang. The data sampling procedure applied was Nonprobability sample with purposive sampling procedure. There were 100 respondents that serves as samples in this study. This study uses data analysis approach in classic assumptions test, path analysis, and mediation test using the help of IBM SPSS software. Findings of this study are that: 1) EWOM on Instagram has a positive and significant effect on purchase intention on Mixue; 2) EWOM on Instagram has a positive and significant effect on Brand Awareness on Mixue; 3) Brand Awareness has a positive and significant effect on purchase intention on Mixue; 4) Brand Awareness has a positive but insignificant effect as intervening variable between brand awareness and purchase intention on Mixue. Keywords: EWOM, Social Media, Brand Awareness, purchase intention.